First Peruvian series of assisted reproduction with highly complex procedures. - Prazak, Ladislao (2015)
Here are the first Peruvian series achieved entirely in our country, marking the beginning of a new era in medical breakthrough that helps the couple to get the son failed. For the first Peruvian series of Assisted Fertilization by highly complex procedures, they were selected 20 couples who had received several infertility treatments for a minimum of 48 months before being incorporated into the program.